Teaching and Learning in Italian Multicultural School Contexts: Outdoor Education and Inclusion Processes for Children with Migrant Backgrounds - Natalini, Alessandra (International Education Trend Issues, 2024)
Italy has recently and rapidly become a country of immigration with an increase in school contexts, especially of second-generation children, leading to the need to deal with the issue of inclusion. This contribution aims to enclose the scientific literature that addresses the inclusion of children with a migrant background within the national school context. After analyzing the ministerial documents and the literature that address this issue, the school context at the local level will be investigated, emphasizing the challenges that teachers must face within increasingly multicultural school contexts, in which they must cope with the numerous needs deriving from the relationship with CNI families and the management of cultural diversity at school.